AB0263 Serum levels of CXCL13 are associated with ultrasonographic synovitis and predict power doppler persistence in early rheumatoid arthritis treated with non-biological disease-modifying anti-rheumatic drugs. (23rd January 2014) - Manzo, A.; Bugatti, S.; Benaglio, F.; Klersy, C.; Vitolo, B.; Todoerti, M.; Sakellariou, G.; Montecucco, C.; Caporali, R.
Abstract : Background: The course of rheumatoid arthritis (RA) varies considerably among different patients. To optimise management, individual's outcomes need to be recognised as early as possible. Novel biological markers specifically reflecting the severity of synovial inflammation at presentation could be more predictive than routine clinical and laboratory assessments. Objectives: To investigate whether baseline serum levels of CXCL13, a chemokine critically involved in RA pathogenesis through B and T cell recruitment and cooperation within lymphoid and extra-lymphoid sites (1, 2), can predict clinical and ultrasonographic (US) outcomes in patients with recent-onset RA. Methods: Study subjects were 161 early RA patients (disease duration <12 months) treated according to a disease activity score (DAS) driven step-up protocol aiming at DAS <2.4. Clinical disease activity measures were collected at baseline, 2, 4, 6, 9 and 12 months, and US examination of the hands was performed at baseline, 6 and 12 months. Grey-scale (GS) and Power Doppler (PD) synovitis were scored (0–3), with overall scores as the sum of each joint score. CXCL13 levels were measured at baseline by enzyme-linked immunosorbent assay and evaluated in relation to the achievement of low disease activity (LDA, DAS <2.4) and US residual inflammation (PD ≤1) at 12 months. Results: Baseline levels of CXCL13 were significantly higher in RA compared to healthy controls (n.19) (p=0.03) and correlated with objective measures of synovitis, such as the swollen joint count (rho 0.28, p<0.001), the US-GS (rho 0.27, p=0.003) and US-PD (rho 0.26, p=0.005) score. Differently from acute phase reactants, CXCL13 showed further correlation with the autoantibody status [median CXCL13 levels in ACPA-positive patients 96.8 pg/ml (IQR 56.4-184.2) vs 68.5 pg/ml (IQR 43.5-105.9) in ACPA-negative patients, p=0.001]. Although CXCL13 did not predict the likelihood of achieving clinical LDA at 12 months within a structured treat-to target protocol, elevated levels of CXCL13 were associated with more frequent increases of methotrexate dosage (p<0.001). Using adjusted analyses, the highest levels of CXCL13 (>100 pg/ml) were the only independent predictor of residual imaging inflammation (p=0.005), irrespective of initial US-PD scores, disease activity status, acute phase reactants and autoantibodies. Among the patients in clinical LDA at 12 months, US-PD scores ≤1 were less frequently achieved in the high baseline CXCL13 (>100 pg/ml) group, with an adjusted OR=0.06 (95%CI 0.01-0.55, p=0.01). Conclusions: CXCL13 emerges as a new biological marker in early RA, accurate in assessing the severity of synovitis and the persistence of US-PD activity over time in response to conventional treatments. References: Manzo A, Vitolo B, Humby F, et al.Mature antigen-experienced T helper cells synthesize and secrete the B cell chemoattractant CXCL13 in the inflammatory environment of the rheumatoid joint.Arthritis Rheum 2008;58:3377-87. Manzo A, Bombardieri M, Humby F, et al. Secondary and ectopic lymphoid tissue responses in rheumatoid arthritis: from inflammation to autoimmunity and tissue damage/remodeling.Immunol Rev 2010;233:267-85. Disclosure of Interest: None Declared